Rose Gorrell making a hat storage mount - Unidentified photographer (Colorado State University. Libraries, 2019)
Photograph of graduate student Rose Gorrell making a storage mount for a hat from the collection during a class in 2019.
Keywords: Fashion -- History; Fashion -- Exhibitions